Knowledge of testicular cancer and practice of testicular self-examination among undergraduate male students during pre and post intervention - Zahidi, Mohd. Yusuf; Ahmad, Azmir (IIUM Press, 2024)
Background: The less promotion on testicular self examination (TSE) among men may contribute to the increase in testicular cancer cases (TC). While TSE could contribute to early detection of TC, its practice is disappointing among young adults. This study aimed to compare the level of knowledge and practice of TC and TSE, respectively, among IIUM Kuantan undergraduate male students at pretest and post-test of educational intervention. Methods: Data collection for pre-test was conducted among 245 male students using a selfadministered questionnaire. Videos regarding TC and TSE were given to the respondents as educational intervention. A post-test questionnaire was distributed among the respondents after two weeks of intervention. Knowledge and practice levels at pretest and posttest phases and their association with Kulliyyah background were statistically analyzed. Results: The score level of knowledge and practice on TC and TSE were 35.31 ± 3.16 and 16.65 ± 3.42, respectively, at pre-test, indicated borderline level between low and high. The post-test showed a significant improvement (p<0.05) in the level of knowledge and practice on TC and TSE with score level of 36.79 ± 2.63 and 18.98 ± 4.60, respectively. There was no significant difference between these results and Kulliyyah background. Conclusion: The study showed a significant improvement in the level of knowledge and practice of TC and TSE, respectively, among undergraduate male students in IIUM Kuantan Campus. Thus, this study provides a preliminary result on importance of promoting TC and TSE among young adults as a preventive measure in curbing the TC cases from increasing.